PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGA TERHADAP KEPUASAN KONSUMEN PADA HOTEL NEW HOLLYWOOD PEKANBARU - Ardianto, Riki; Sutrisna, Endang (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
This research was conducted at Hotel New Hollywood Pekanbaru located at Jalan Kuantan Raya No. 120, Pekanbaru. The purpose of this study was to determine the effect of service quality and pricing on consumer satisfaction at Hotel New Hollywood Pekanbaru partially and simultaneously. In this research the method used is quantitative descriptive analysis with SPSS program. The population in this study were all visitors staying at the Hotel New Hollywood Pekanbaru in the last year of 2018 totaling 23,585 people. Where the samples in this study were Hotel New Hollywood Pekanbaru consumers as many as 100 respondents. To determine the sample using the Slovin formula, a non-probability sampling technique with an accidental sampling technique. Data collection techniques through interviews and questionnaires, types and sources of data using primary data and secondary data, measurement techniques using a Likert scale.From the analysis of data which includes validity, reliability, simple linear analysis, multiple linear analysis, determination analysis and significance test with t test (partial test), and F test (simultaneous). The results of this study indicate that the results of the first t test hypothesis testing, service quality on customer satisfaction is t arithmetic (6,782)> t table (1,6605) means that service quality has a significant effect on customer satisfaction. second, price fixing on customer satisfaction is t arithmetic (6,965)> t table (1,6605) means that price setting has a significant effect on customer satisfaction. F Test Results of service quality have a significant effect on customer satisfaction, namely F arithmetic (33,737)> F tables (3,09). This means that service quality and price setting simultaneously have a significant effect on customer satisfaction at Hotel New Hollywood Pekanbaru. Keywords: Service Quality, Pricing, Consumer Satisfaction